Selenium enriched bifidobacteria and lactobacilli as potential dietary supplements - Mrvikova, Iva; Hyrslova, Ivana; Kana, Antonin; Kantorova, Vera; Lampová, Barbora; Doskocil, Ivo; Krausova, Gabriela (World journal of microbiology & biotechnology incorporating the MIRCEN Journal of applied microbiology and biotechnology, 2024)
In this study, we tested the ability of lactobacilli and bifidobacteria strains to accumulate and biotransform sodium selenite into various selenium species, including selenium nanoparticles (SeNPs). Selenium tolerance and cytotoxicity of selenized strains towards human adenocarcinoma Caco-2 and HT29 cells were determined for all tested strains. Furthermore, the influence of selenium enrichment on the antioxidant activity of selenized strains and hydrophobicity of the bacterial cell surfaces were evaluated. Both hydrophobicity and antioxidant activity increased significantly in the selenized L. paracasei strain and decreased significantly in the selenized L. helveticus strain. The concentrations of 5 and 10 mg/L Na2SeO3 in the growth media were safer for Caco-2 and HT29 cell growth than higher concentrations. At higher concentrations (30, 50, and 100 mg/L), the cell viability was reduced. All the tested strains showed differences in antioxidant potential and hydrophobicity after selenium enrichment. In addition to selenocystine ​​and selenomethionine, the tested bacterial strains produced significant amounts of SeNPs. Our results show that the tested bacterial strains can accumulate and biotransform inorganic selenium, which allows them to become a potential source of selenium.
Keywords: potravní doplňky; Antioxidants; Dietary Supplements; Caco-2 buňky; selen; Selenium; antioxidancia; Lactobacillus; Caco-2 Cells; Humans; lidé